Does perioperative intravenous dextrose reduce postoperative nausea and vomiting? A systematic review and meta-analysis - Kim SH; Kim DH; Kim EJ; HJ Kim; Choi YS (Dove Medical Press, 2018)
Seung Hyun Kim,1 Do-Hyeong Kim,2 Eungjin Kim,1 Hyun Jung Kim,3,* Yong Seon Choi2,* 1Department of Anesthesiology and Pain Medicine, Severance Hospital, Yonsei University College of Medicine, Seoul, Korea; 2Department of Anesthesiology and Pain Medicine, Anesthesia and Pain Research Institute, Severance Hospital, Yonsei University College of Medicine, Seoul, Korea; 3Department of Preventive Medicine, College of Medicine, Institute for Evidence-based Medicine, Korea University, Seoul, Korea *These authors contributed equally to this work Purpose: Perioperative dextrose-containing fluid administration has been used as a non-pharmacologic preventive measure against postoperative nausea and vomiting (PONV), a common and distressing complication of anesthesia. However, its efficacy remains unclear as previous studies reported inconsistent results. Our objective was to compare dextrose-containing fluid with non-dextrose-containing fluid in terms of PONV for 24 hours after surgery under general anesthesia. The effects of dextrose according to different types of surgery and the fluid volume were also examined.Methods: We performed a systematic review and meta-analysis of randomized controlled trials (RCTs) comparing dextrose-containing fluid with non-dextrose-containing fluids after general anesthesia in terms of PONV incidence and the need for rescue anti-emetic therapies for 24 hours after surgery. A literature search was performed, using Medline, EMBASE, Cochrane Central Register of Controlled Trials, Web of Science, and Scopus, up to February 2018.Results: We included seven RCTs. Compared with the control group, perioperative dextrose administration did not reduce the risk for PONV, with a relative risk (RR) of 0.72 (95% CI: 0.50–1.03). However, perioperative dextrose reduced the requirement for anti-emetics, compared with the control group, with a RR of 0.60 (95% CI: 0.44–0.83). The quality of evidence in this meta-analysis was poor due to high risks of selection and performance biases and substantial statistical heterogeneity. After subgroup analysis, the risk for PONV was reduced in patients who had undergone laparoscopic cholecystectomy, but not other surgeries, and the effects of dextrose on the risk for PONV did not differ according to the fluid volume administered.Conclusion: Perioperative intravenous (i.v.) dextrose did not reduce the risk for PONV. However, it did reduce the need for anti-emetics after general anesthesia. Furthermore, the effects of dextrose varied according to the surgery type. Further studies are needed to determine the benefits of perioperative i.v. dextrose administration as a preventive measure against PONV. Keywords: general anesthesia, PONV, dextrose, laparoscopic cholecystectomy